Impact of “new” global trade regimes on retional integration processes in the south - Adetula, Victor Adebola O. (APISA, 2021)
The critical question is how integration and cooperative schemes are they fairing (or are likely to fare) under the "new" global regimes on trade? The Economic Community of West African States (ECOWAS) is our case study for testing our key hypotheses on the challenges and opportunities for the regional integrations schemes in the South against the background of ‘new’ global trade regimes. We examine the paths taken by countries in West Africa to bring about regional cooperation and integration and ask the question what is the impact of globalization, especially in terms of the pressures of global market forces on integration processes in the South.